Pengembangan Teknologi dalam Bidang Kesehatan - Mafaza Cahya Yuniar; Safila, Melisa Intan; Mohamad Putra; Muhammmad Haidar Asyraf; Nahdiyah Dwi Amelia; Dion Kunto Adi Patria (POLTEKKES KEMENKES YOGYAKARTA, 2022)
In today's era of globalization, technological progress has expanded rapidly. One notable area of technological advancement is in the health field. In this era, people can access health information services through various media as a solution to health problems. One such advancement in information technology is seen in the health sector, including in medicine. The rapid progress in health technology has led to the development of numerous applications that support hospital organizations, medical practice, and health sciences research. This study, titled